Inserção e indução à docência no Mato Grosso : percepções de professores iniciantes em narrativas - Clemente, Adriana dos Reis (2020)
This research is associated with the Graduate Program in Education (PPGEdu), in the line of research entitled Teacher Training and Educational Public Policies, from the Federal University of Mato Grosso (MT), Campus de Rondonópolis. The purpose was to deepen the knowledge on the theme “The beginning of teaching”, with its delimitation “The paths taken by the beginner teacher in public schools in Rondonópolis/MT”, in particular, his experiences in induction practices, offered by the public education networks (municipal and state), in the municipality of Rondonópolis. To this end, the following question was raised: how does the process of professional induction of the public school teacher (State and Municipal) of Rondonópolis/MT takes place, in the search to know the paths taken in the professional insertion of beginning teachers? In view of the research outline and problem presented, the general aim was to understand the process of inducing teaching, originating from initiatives of the teaching networks (State and Municipal), in response to the real needs of the beginning teacher, in his professional insertion and developments. of these training actions. In this process, some questions guided the research: How do the actions of welcoming and inducing teaching networks (State and Municipal) take place from the perspective of beginning teachers? Have the proposals of the education networks (State and Municipal), for beginning teachers, contributed to the professional development of the participants? How do these professionals enroll in the teaching career? Is there an exchange of information and experiences between the beginning teacher and his peers? The research was dedicated to the knowledge of the entry of the beginning teacher in the school context, that is, in welcoming; in the administrative, pedagogical guidelines and in the relationships established with peers, with regard to the information, the exchange of knowledge, in short, the experiences lived in the school environment and in the experiences that involve the professional induction of professionals in the initial years of Basic Education, especially, in the paths taken by the teachers, in the professional development that begins and its consequences. The participants in this scientific work have up to five years of experience. As a methodological path, (auto) biographical research was adopted, privileging the qualitative approach, with autobiographical narratives and autobiographical interviews as data collection instruments. The result of the data analysis showed dilemmas, expectations, and challenges at the beginning of the teaching career, such as dealing with data entry in the system, managing the time of activities, among others, as well as the importance of monitoring by the management team and/or experienced teacher to the beginner teacher in the first contacts with the school reality, which brings this research closer to others that focus on professional insertion. The research data also reveal that the actions to induce teaching carried out by the Municipal Department of Education (SEMED) and the State Department of Education, Sports and Leisure of Mato Grosso (SEDUC) in Rondonópolis/MT, are timid. SEMED develops more specific actions to induce the beginner teacher and SEDUC has developed the training matrix for the beginner and is developing the training policy. There is still no policy to induce teaching, although there is an effort for the actions to become public policy. The results indicate the need to implement a policy to induce teaching, which meets the training needs of beginning teachers as an aid in facing the challenges of the beginning of the teaching career.